Implementation of a Zero-Voltage-Switching and Zero-Current-Switching Interleaved Boost and Buck Converter (International Journal of Engineering and Computer Science, 2014)
A novel interleaved boost and buck converter with zero-voltage switching (ZVS) and zero-current switching (ZCS) characteristic is proposed in this paper. By using the interleaved approach, this topology not only decreases the current stress of the main circuit device but also reduces the ripple of the input current and output voltage. Moreover, by establishing the common soft-switching module, the soft-switching interleaved converter can greatly reduce the size and cost. The main switches can achieve the characteristics of ZVS and ZCS simultaneously to reduce the switching loss and improve the efficiency with a wide range of load. This topology has two operational conditions depending on the situation of the duty cycle. The operational principle, theoretical analysis, and design method of the proposed converter are presented. Finally, simulations results are used to verify the feasibility and exactness  of the proposed converter.